Pharmacological Enhancement of α-Glucosidase by the Allosteric Chaperone N-acetylcysteine - Porto, Caterina (Nature Publishing Group, 2012)
Pompe disease (PD) is a metabolic myopathy due to the deficiency of the lysosomal enzyme α-glucosidase (GAA). The only approved treatment for this disorder, enzyme replacement with recombinant human GAA (rhGAA), has shown limited therapeutic efficacy in some PD patients. Pharmacological chaperone therapy (PCT), either alone or in combination with enzyme replacement, has been proposed as an alternative therapeutic strategy. However, the chaperones identified so far also are active site-directed molecules and potential inhibitors of target enzymes. We demonstrated that N-acetylcysteine (NAC) is a novel allosteric chaperone for GAA. NAC improved the stability of rhGAA as a function of pH and temperature without disrupting its catalytic activity. A computational analysis of NAC–GAA interactions confirmed that NAC does not interact with GAA catalytic domain. NAC enhanced the residual activity of mutated GAA in cultured PD fibroblasts and in COS7 cells overexpressing mutated GAA. NAC also enhanced rhGAA efficacy in PD fibroblasts. In cells incubated with NAC and rhGAA, GAA activities were 3.7–8.7-fold higher than those obtained in cells treated with rhGAA alone. In a PD mouse model the combination of NAC and rhGAA resulted in better correction of enzyme activity in liver, heart, diaphragm and gastrocnemia, compared to rhGAA alone.